2020
DOI: 10.15453/2168-6408.1622
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation as Key Factor in Protection Against the Harmful Effects of Adverse Childhood Experiences: Critical Role for Occupational Therapists

Abstract: The author reports that they have no conflicts of interest to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This preliminary study aimed to explore EFs, self-efficacy, anxiety, and sensory modulation in mothers of children with ADHD, attempting to better understand factors affecting their co-regulation abilities [ 25 , 36 , 50 , 76 , 77 ]. This study found enhanced sensory under-responsiveness in mothers of children with ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This preliminary study aimed to explore EFs, self-efficacy, anxiety, and sensory modulation in mothers of children with ADHD, attempting to better understand factors affecting their co-regulation abilities [ 25 , 36 , 50 , 76 , 77 ]. This study found enhanced sensory under-responsiveness in mothers of children with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is crucial for developing regulatory abilities and enhancing child motivation [ 24 , 48 ]. Importantly, maternal stress impacts the perception of maternal roles and elicits increased feelings of low competence, negatively affecting the mother’s ability to support her child and thus disrupting the parent–child relationship [ 50 ]. Indeed, parents of children with ADHD report feeling incompetent and having lower parental self-efficacy in comparison with parents of children without ADHD [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention at the environmental level may include creating optimal environments to support development (e.g., parent education). Finally, promoting healthy habits, routines, and roles creates a positive identity for the child and parent through occupation (Whitney, 2020). Despite this, there is limited evidence demonstrating the effectiveness of occupational therapy interventions in working with children with a history of ACEs outside the medical arena and in community settings.…”
Section: Introductionmentioning
confidence: 99%
“…The literature articulates occupational therapists' role in applying sensory-based techniques in the inpatient setting and how practitioners can address trauma through the person, environment, and occupation. For example, Whitney (2020) advises intervening at the person level (with the child or caregiver-child dyad) through self-regulation and co-regulation strategies (e.g., teaching mindfulness). Intervention at the environmental level may include creating optimal environments to support development (e.g., parent education).…”
Section: Introductionmentioning
confidence: 99%